Diet and high altitude strongly drive convergent adaptation of gut microbiota in wild macaques, humans, and dogs to high altitude environments - Zhao, Junsong; Yao, Yongfang; Dong, Mengmeng; Xiao, Hongtao; Xiong, Ying; Yang, Shengzhi; Li, Diyan; Xie, Meng; Ni, Qingyong; Zhang, Mingwang; Xu, Huailiang (Frontiers in Microbiology, 2023)
Animal gut microbiota plays an indispensable role in host adaptation to different altitude environments. At present, little is known about the mechanism of animal gut microbiota in host adaptation to high altitude environments. Here, we selected wild macaques, humans and dogs with different levels of kinship and intimate relationships in high altitude and low altitude environments, and analysed the response of their gut microbiota to the host diet and altitude environments. Alpha diversity analysis found that at high altitude, the gut microbiota diversity of wild macaques with more complex diet in the wild environments is much higher than that of humans and dogs with simpler diet (P < 0.05), and beta diversity analysis found that the UniFrac distance between humans and dogs was significantly lower than between humans and macaques (P < 0.05), indicating that diet strongly drive the convergence of gut microbiota among species. Meanwhile, alpha diversity analysis found that among three subjects, the gut microbiota diversity of high altitude population is higher than that of low altitude population (ACE index in three species, Shannon index in dog and macaque and Simpson index in dog, P < 0.05), and beta diversity analysis found that the UniFrac distances among the three subjects in the high altitude environments were significantly lower than in the low altitude environments (P < 0.05). Additionally, core shared ASVs analysis found that among three subjects, the number of core microbiota in high altitude environments is higher than in low altitude environments, up to 5.34 times (1105/207), and the proportion and relative abundance of the core bacteria types in each species were significantly higher in high altitude environments than in low altitude environments (P < 0.05). The results showed that high altitude environments played an important role in driving the convergence of gut microbiota among species. Furthermore, the neutral community model trial found that the gut microbiota of the three subjects was dispersed much more at high altitude than at low altitude, implying that the gut microbiota convergence of animals at high altitudes may be partly due to the microbial transmission between hosts mediated by human activities.